Effects of anaesthesia on thyroxine and thyroid-stimulating hormone levels in dogs - Glanemann, B.; Gaut, N.; Neiger, R. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2008)
Objective: Although hypothyroidism is a common endocrinopathy in dogs, the diagnosis is not always straightforward. Several factors, including systemic disease or administration of drugs, can affect thyroid function and may lead to erroneous test results. The aim of this study was to evaluate if anaesthesia has an effect on total thyroxin (TT4) or thyroid-stimulating hormone (cTSH) levels in dogs. Material and methods: Twenty-four dogs presented for various primary problems underwent anaesthesia for endoscopy. Four different anaesthetic protocols using a combination of propofol and isoflurane, propofol and halothane, thiopental and isoflurane or thiopental and halothane (each n = 6) were randomly chosen for each dog. TT4 and cTSH levels were measured before and 24 hours after anaesthesia. Results: Post-anaesthetic TT4 levels were significantly lower than pre-anaesthetic levels (p = 0.0002). There was no significant difference between the four anaesthetic groups (p = 0.17). The post-anaesthetic cTSH values were not significantly (p = 0.73) different compared to the pre-anaesthetic values. Conclusions: Results indicate that TT4 values may significantly decrease for at least 24 hours post recovery from anaesthesia irrelevant of the anaesthetic agent used. Clinical relevance: The study has highlighted that thyroid testing in dogs should always be viewed in light of the clinical situation. General anaesthesia can lower TT4 levels to a point where hypothyroidism may be wrongly diagnosed.
Keywords: Hypothyroidism; endocrine disease; euthyroid sick syndrome; endoscopy